Evaluation of histidine-containing dipeptides in twelve marine organisms and four land animal meats by hydrophilic interaction liquid chromatography with ultraviolet detection. Issue 13 (27th August 2018) - Mori, Akihiro; Hikihara, Risako; Ishimaru, Mami; Hatate, Hideo; Tanaka, Ryusuke
Abstract: Histidine-containing dipeptides (HCDP) are widely distributed in the skeletal muscle of vertebrates, including marine and terrestrial organisms. In this study, we developed a simple, rapid, and accurate method for identifying HCDP by high performance liquid chromatography (HPLC) with isocratic elution. The method based on hydrophilic interaction chromatography (HILIC) using phosphorylcholine HILIC column (250 mm × 4.6 mm, 5 µm particles), 15 mmol/L ammonium acetate (pH 4.25):acetonitrile:methanol (3.5:5.85:0.65 by volume) as the mobile phase at 1.0 mL/min, and ultraviolet detection at 214 nm. As a result, HCDP, such as carnosine, balenine, and anserine, were separated in 20 min and the results were sufficiently reproducible and quantitative. Using this method, the limit of detection (LOD) was superior to previous methods. The LOD of carnosine, balenine, and anserine were 0.062, 0.085, and 0.100 µg/mL. The linearity range of carnosine, balenine, and anserine were 0.207–500, 0.283–500, and 0.334–500 µg/mL. The average recovery of that were 99.9, 91.7, and 100.1%. Our method was used to evaluate HCDP in marine and terrestrial organisms. Large pelagic migratory fish contained large amounts of anserine. Both land and aquatic mammals contained large amounts of carnosine compared with fish. Balenine was quantitated in minke whales, Japanese eels, pigs, and chickens. Graphical Abstract: